Inhibitory Effect of Dihydroartemisinin on the Proliferation and Migration of Melanoma Cells and Experimental Lung Metastasis From Melanoma in Mice - Zhang, Qi; Jin, Linbo; Jin, Quanxin; Wei, Qiang; Sun, Mingyuan; Yue, Qi; Liu, Huan; Li, Fangfang; Li, Honghua; Ren, Xiangshan; Jin, Guihua (Frontiers in Pharmacology, 2021)
Melanoma is aggressive and can metastasize in the early stage of tumor. It has been proved that dihydroartemisinin (DHA) positively affects the treatment of tumors and has no apparent toxic and side effects. Our previous research has shown that DHA can suppress the formation of melanoma. However, it remains poorly established how DHA impacts the invasion and metastasis of melanoma. In this study, B16F10 and A375 cell lines and metastatic tumor models will be used to investigate the effects of DHA. The present results demonstrated that DHA inhibited the proliferative capacity in A375 and B16F10 cells. As expected, the migration capacity of A375 and B16F10 cells was also reduced after DHA administration. DHA alleviated the severity and histopathological changes of melanoma in mice. DHA induced expansion of CD8+CTL in the tumor microenvironment. By contrast, DHA inhibited Treg cells infiltration into the tumor microenvironment. DHA enhanced apoptosis of melanoma by regulating FasL expression and Granzyme B secretion in CD8+CTLs. Moreover, DHA impacts STAT3-induced EMT and MMPS in tumor tissue. Furthermore, Metabolomics analysis indicated that PGD2 and EPA significantly increased after DHA administration. In conclusion, DHA inhibited the proliferation, migration and metastasis of melanoma in vitro and in vivo. These results have important implications for the potential use of DHA in the treatment of melanoma in humans.